Ecological and ecotoxicological responses in the assessment of the ecological status of freshwater systems: A case-study of the temporary stream Brejo of Cagarrão (South of Portugal) - Palma, Patrícia (2018)
The objective of the study was to assess the integrated use of macroinvertebrate indexes and ecotoxicological parameters in the evaluation of the ecological status of a temporary stream with a strong agricultural influence. Water quality was analysed at two sampling sites along the stream, considering: chemical supporting parameters; hazardous substances (pesticides); benthic macroinvertebrate communities, through quality (Iberian Biological Monitoring Working Party and Iberian Average Score Per Taxon) and multi-metric indices (Southern Portuguese Index of Invertebrates and Ecological Quality Ratio); and ecotoxicological responses using lethal and sub-lethal bioassays. The water chemical characterization showed high levels of organic matter and nutrients, mainly in the dry period ((biochemical oxygen demand (BOD5): 18.5-25.5mgL-1, chemical oxygen demand (COD): 60.8-193.7mgL-1; total phosphorus (TP): 0.17-0.33mgL-1)), which may compromise the support of biological life. In accordance with the physicochemical results, the stream had an ecological status less than good. Of the 25 pesticides analysed, only five, namely terbuthylazine, 2-methyl-chlorophenoxyacetic acid, bentazone, mecoprop and metolachlor were quantified. In general, the concentrations of pesticides detected were low, except at the source of the stream in January 2012 (sum of pesticides 2.29μgL-1), mainly due to the concentration of bentazone (1.77μgL-1), both values surpassing the European Commission threshold values. The analysis of benthic macroinvertebrates showed low levels of abundance and family diversity, with communities dominated by resistant groups to organic pollution and pesticides, such as the Chironomidae family. In general, the reproduction ecotoxicological results showed a very marked decrease in the number of juveniles per female. The Spearman correlation identified pesticides, namely MCPA (R=-0.89; p<0.05), as the main responsible for the observed effect. The results showed the linearity and complementarity of the two groups of biological responses, allowing to cover the interactions between the ecosystem's species and the different types of pollutants.